The Beefcake and the Beast: Professionalization, Mediatization, and the Representations of Masculinity in French Rugby. Issue 3 (3rd July 2022) - Dalla Pria, Yan; Bonnet, Christophe
ABSTRACT: The purpose of this article is to examine the influence of professionalization and mediatization of rugby on the representations of masculinity in this sport over the last quarter century. Data used for both statistical analysis (using chi-square tests of independence and Multiple Correspondence Analysis) and qualitative content analysis were collected in France through a corpus of 799 rugby-related advertisements mainly dating from 1987 to 2015. The authors demonstrate that, alongside the hegemonic masculinity produced by the socialization of rugby players until the 1980s (the "Beast"), the marketization of elite rugby that began in the 1990s has led to the emergence of an alternative figure of masculinity that values aesthetics over physical strength (the "Beefcake"). The authors theorize this hybridization as a way for rugby players, who follow the lead of advertisers and communications agencies, to distance themselves from the increasingly stigmatized figure of masculinity embodied by their sport in order to entice new audiences. Simultaneously, while allowing them to seize the financial manna of advertising, this rebranding reveals the plasticity of the hegemonic masculinity conveyed by rugby, which is able to regenerate itself by evolving with the times. Based on this case, the authors then discuss the dialectic relationship between the hegemonic model and hybrid masculinities in both a synchronic and a diachronic perspective.